التأثيرات المحتملة للغاز الصخري على التنمية المستدامة إشارة لحالة الجزائر - صابة, / بوبكر; بن حسين, د / ناجي (Sciences humaines, 2016)
أثارت مسألة استغلال الغاز غير التقليدي، خاصة الغاز الصخري الكثير من النقاش والجدل بين المختصين     في الصناعة البترولية والناشطين في المجال البيئي نظرا للمخاطر المحتملة التي يمكن أن يسفر عنها استخراج الغاز غير التقليدي. يحاول الباحثان في هذه الدراسة تحديد إذا ما كان استخراج الغاز الصخري يستجيب لمعايير التنمية المستدامة ويحقق أهدافها أم لا. توصل الباحثان إلى أن استخراج واستغلال الغاز غير التقليدي لا يتعارض مع التنمية المستدامة.   الكلمات المفتاحية: الغاز الصخري ، التنمية المستدامة، الآثار  البيئية.           The issue of extracting unconventional gas, particularly shale gas has raised many concerns worldwide about the potential environmental risks and damages associated with its extraction and exploitation. Algeria is not an exception to that, the government’s willing to invest in shale gas has generated a fierce opposition by environmentalists as well as politicians. The present paper attempts to determine whether the extraction and exploitation of shale gas is environmentally friendly. Contrary to what one would expect shale gas extraction and exploitation is consistent with the sustainable development concept. Key words: shale gas, sustainable development, environmental effects .